Lactobacillus acidophilus attenuates Aeromonas hydrophila induced cytotoxicity in catla thymus macrophages by modulating oxidative stress and inflammation. (July 2016) - Patel, Bhakti; Kumar, Premranjan; Banerjee, Rajanya; Basu, Madhubanti; Pal, Arttatrana; Samanta, Mrinal; Das, Surajit
Graphical abstract: Highlights: The pathogenicity of A. hydrophila in catla thymus macrophage is elucidated. A. hydrophila induces CTM cell cytotoxicity by inducing ROS accumulation. Pretreatment of CTM cells with L. acidophilus restored cell viability by reducing ROS. L. acidophilus pre-treatment in CTM cells ameliorated iNOS and COX2 expression. L. acidophilus attenuated A. hydrophila- induced apoptosis in CTM cells. Abstract: The pathogenesis of Aeromonas hydrophila, a potent fish pathogen, is attributed to its ability to cause motile aeromonad septicaemia leading to apoptosis in a myriad of fish species, including freshwater carp Catla catla . However, the underlying mechanism of antagonistic activity of probiotics against A. hydrophila induced apoptosis is not elucidated due to lack of appropriate in-vitro models. This study reported that the exposure of catla thymus macrophages (CTM) to A. hydrophila markedly induced cellular injuries as evidenced by elevated levels of reactive oxygen species (ROS), reactive nitrogen species (RNS), increased apoptosis, DNA damage and decreased cellular viability. Flow cytometry analysis and Annexin-V/propidium iodide assay further confirmed increased ROS positive cells leading to cell death after infection. The quantitative real-time PCR analysis, also revealed upregulation of inducible nitric-oxide synthase (iNOS), pro-inflammatory cytokine (TNFα), cyclooxygenase2 (COX-2) and downregulation of anti-inflammatory cytokine (IL-10). Pretreatment of cells with probiotic, Lactobacillus acidophilus attenuated A. hydrophila induced apoptosis as evident from the decrease in the levels of ROS, RNS and DNA damage. Significant increase ( P ≤ 0.05 ) in expression of TNFα and IL-10 and decrease in iNOS and COX-2 was observed on probiotic stimulation. In-vivo study using catla fingerlings confirmed similar pattern of ROS, iNOS, NO production and cytokine expression in thymus. This study provides a comprehensive insight into the mechanistic basis of L. acidophilus induced macrophage mediated inflammatory response against A. hydrophila in CTM cells. Further, it speculates the possibility of using cost-effective in-vitro models for screening probiotic candidates of therapeutic potential in aquaculture industry.